2013
DOI: 10.1186/1741-7007-11-80
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparumencodes a conserved active inhibitor-2 for Protein Phosphatase type 1: perspectives for novel anti-plasmodial therapy

Abstract: BackgroundIt is clear that the coordinated and reciprocal actions of kinases and phosphatases are fundamental in the regulation of development and growth of the malaria parasite. Protein Phosphatase type 1 is a key enzyme playing diverse and essential roles in cell survival. Its dephosphorylation activity/specificity is governed by the interaction of its catalytic subunit (PP1c) with regulatory proteins. Among these, inhibitor-2 (I2) is one of the most evolutionarily ancient PP1 regulators. In vivo studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(85 citation statements)
references
References 73 publications
5
80
0
Order By: Relevance
“…In a previous study, we clearly showed the implication of K 12 TISW 16 (‘RVxF’ motif, motif 1) using biochemical and functional approaches , supporting the NMR data presented here. In order to further inspect the contribution of F 95 KEKRK 100 (‘FxxR/KxR/K’ motif, motif 2) present in the region D94–T117 immobilized by PfPP1 interaction, we mapped the interaction site(s) of PfI2 mutated on motif 2 (F95, K98 and K100 were replaced by A) with PfPP1 using NMR spectroscopy under the same conditions as for the wild‐type PfI2 protein.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In a previous study, we clearly showed the implication of K 12 TISW 16 (‘RVxF’ motif, motif 1) using biochemical and functional approaches , supporting the NMR data presented here. In order to further inspect the contribution of F 95 KEKRK 100 (‘FxxR/KxR/K’ motif, motif 2) present in the region D94–T117 immobilized by PfPP1 interaction, we mapped the interaction site(s) of PfI2 mutated on motif 2 (F95, K98 and K100 were replaced by A) with PfPP1 using NMR spectroscopy under the same conditions as for the wild‐type PfI2 protein.…”
Section: Resultssupporting
confidence: 90%
“…). These data showed that motif 2 is also essential for the regulation of PfPP1 activity by PfI2, as demonstrated previously for motif 1 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…I-2 was first identified as one of two heat-stable proteins from rabbits that can inhibit the activity of PP1 [9]. I-2 like activity has since been found in diverse organisms, from GLC8 in yeast to I-2 in Rabbit, Caenorhabditis elegans, Drosophila, Plasmodium falciparum, and humans [5,13,16]. A plenty of evidence indicated that I-2 function was regulated by phosphorylation.…”
Section: Introductionmentioning
confidence: 99%